2009
DOI: 10.1037/a0013778
|View full text |Cite
|
Sign up to set email alerts
|

Attentional processes in stereotype formation: A common model for category accentuation and illusory correlation.

Abstract: Stereotype formation may be based on the exaggeration of real group differences (category accentuation) or the misperception of group differences that do not exist (illusory correlation). This research sought to account for both phenomena with J. K. Kruschke's (1996Kruschke's ( , 2001Kruschke's ( , 2003 attention theory of category learning. According to the model, the features of majority groups are learned earlier than the features of minority groups. In turn, the features that become associated with a minor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
98
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(106 citation statements)
references
References 58 publications
7
98
0
1
Order By: Relevance
“…Another inverse base-rate study also demonstrated an attentional preference for rare associations as measured via ERP correlates of selective attention (Wills, Lavric, Hemmings, & Surrey, 2014). Another study that was very similar to the present ones, but showing the inverse baserate effect in the formation of group impressions (i.e., stereotypes), showed that participants paid more attention to rare rather than common behaviors when learning about minority group members (Sherman et al, 2009). Although these studies support the attentional mechanism, the current research would benefit from additional studies that directly measure attention when perceivers form context-based impressions.…”
Section: Limitationssupporting
confidence: 50%
See 3 more Smart Citations
“…Another inverse base-rate study also demonstrated an attentional preference for rare associations as measured via ERP correlates of selective attention (Wills, Lavric, Hemmings, & Surrey, 2014). Another study that was very similar to the present ones, but showing the inverse baserate effect in the formation of group impressions (i.e., stereotypes), showed that participants paid more attention to rare rather than common behaviors when learning about minority group members (Sherman et al, 2009). Although these studies support the attentional mechanism, the current research would benefit from additional studies that directly measure attention when perceivers form context-based impressions.…”
Section: Limitationssupporting
confidence: 50%
“…In the same way that people learn to distinguish unique symptoms of diseases, they may also learn how to distinguish unique characteristics of social groups whose members are encountered with different frequency. Sherman et al (2009) tested these predictions in a series of studies that used the inverse base-rate and illusory correlation (Hamilton & Gifford, 1976) paradigms. Their findings were consistent with attention theory predictions: when participants were asked to categorize individuals who possessed both perfect predictor traits (PC + PR), they were more likely to categorize the individual as a minority group member than as a majority group member.…”
Section: Attention Theory and Stereotype Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, their occasional coincidences are very salient, which boosts learning about the relationship between the minority group and the negative behaviors. More recent accounts differ in the details, but they also address the role of learning processes (e.g., Fiedler, 2000;Sherman, Kruschke, Sherman, Percy, Petrocelli, & Conrey, 2009). …”
Section: Iat and Illusion Of Causalitymentioning
confidence: 99%